2021
DOI: 10.1016/j.jbusres.2020.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the special issue – Digital business models: A multi-disciplinary and multi-stakeholder perspective

Abstract: The advent and enormous growth of digital technologies, and associated data, force firms to respond to novel digital challenges and increasingly lead them to transform their existing business models. Importantly, given that digital transformation has a strong impact on multiple disciplines, such as logistics, marketing, and strategy, and involves multiple stakeholders, such as service providers, platforms, employees and end-users, it also requires researchers and businesses to adopt a multi-disciplinary, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 16 publications
0
50
0
9
Order By: Relevance
“…Because the intersection between digital transformation and innovation management is multi‐faceted and multi‐dimensional (Broekhuizen et al, 2021; Hanelt et al, 2020; Hess et al, 2016; Vial, 2019; Zangiacomi et al, 2020), in the next section we introduce a simple framework that identifies three levels of analysis (i.e., macro, meso, and micro) along which the discussion on the contributions to the special issue is organized and structured.…”
Section: Digital Transformation and Innovation Management: Opening Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the intersection between digital transformation and innovation management is multi‐faceted and multi‐dimensional (Broekhuizen et al, 2021; Hanelt et al, 2020; Hess et al, 2016; Vial, 2019; Zangiacomi et al, 2020), in the next section we introduce a simple framework that identifies three levels of analysis (i.e., macro, meso, and micro) along which the discussion on the contributions to the special issue is organized and structured.…”
Section: Digital Transformation and Innovation Management: Opening Upmentioning
confidence: 99%
“…Providing a comprehensive definition of digital transformation is complex because it is a multifaceted (Broekhuizen et al, 2021; Hanelt et al, 2020; Vial, 2019) and multidimensional phenomenon (Hess et al, 2016; Zangiacomi et al, 2020), affecting organizations at different levels and in different forms. Recent research portrays digital transformation as an emerging field of scholarly interest for management and organizational researchers, as well as a new research paradigm (Hanelt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The field of sustainability and viability of operations in SC networks under different uncertain conditions is also being revisited according to current needs [23,24,44]. However, the long-term sustainable solution lies with digitally supported technological help [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have examined the concept of digital transformation, including digital transformation ( Broekhuizen, Broekhuis, Gijsenberg, & Wieringa, 2021 ), digital technologies ( Correani, De Massis, Frattini, Messeni Petruzzelli, & Natalicchio, 2020 ), and digital innovation ( D’Ippolito, Petruzzelli, & Panniello, 2019 ). Researchers suggested that digital transformation is complex because it is a multifaceted ( Vial, 2019 ), multidimensional phenomenon ( Zangiacomi, Pessot, Fornasiero, Bertetti, & Sacco, 2020 ) affecting organizations at different levels and in different forms.…”
Section: Literature Reviewmentioning
confidence: 99%